Does the Introduction of Laparoscopic Distal Pancreatectomy Jeopardize Patient Safety and Well-Being?. (December 2016) - Hasselgren, K.; Halldestam, I.; Fraser, M. P.; Benjaminsson Nyberg, P.; Gasslander, T.; Björnsson, B.
Background/Purpose: Despite retrospective data indicating short-term superiority for laparoscopic distal pancreatectomy compared to open distal pancreatectomy, the implementation of the procedure has been slow. The aim of this study was to investigate whether patients operated with laparoscopic distal pancreatectomy during the early phase of introduction are at higher risk for complications than patients operated with open distal pancreatectomy. Methods: A retrospective single-center analysis of patients operated with laparoscopic distal pancreatectomy (n = 37) from the introduction of the procedure and comparison regarding demographic data, preoperative data, operative factors, and postoperative outcomes to patients operated with open distal pancreatectomy was done. Results: Operation duration shortened (195 vs 143 min, p = 0.04) and severe complications reduced (37% vs 6%, p = 0.02) significantly in the laparoscopic distal pancreatectomy group between the first half of the study and the second half. Blood loss was significantly (p < 0.001) lower in the laparoscopic distal pancreatectomy group (75 mL) than in the open distal pancreatectomy group (550 mL), while complication rate and hospital stay as well as the percentage of radical resections were the same. Conclusion: Laparoscopic distal pancreatectomy can be introduced without jeopardizing patient safety and well-being during the early learning curve. The procedures should be compared in a prospective randomized manner.